80.4k views
12 votes
Write an expression that can be used to produce vector g from vectors e and f Explain how

you determined that expression.

Write an expression that can be used to produce vector g from vectors e and f Explain-example-1

1 Answer

12 votes

Answer:

Explanation:

vector e is (-1,5),f is (3,-4),g is (2,1)

2i+j=x(-i+5j)+y(3i-4j)

2=-x+3y (multiply by 5)

10=-5x+15y

1=5x-4y

add

11=11y

y=1

2=-x+3(1)

x=3-2=1

2i+j=1(-i+5j)+1(3i-4j)

User Ayeshmantha Perera
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.